Genotypic And Phenotypic Characterisation Of Three Local Chicken Ecotypes Of Ghana Based On Principal Component Analysis And Body Measurements. - Botchway, P.K.; Amuzu-Aweh, E.N.; Naazie, A.; Aning, G.K.; Otsyina, H.R.; et al. (Plos One, 2024)
This study aimed to characterise three Ghanaian local chicken ecotypes, namely, Interior Savannah, Forest, and Coastal Savannah, based on morphological data and single nucleo tide polymorphism (SNP) genotypes. Morphological data including body weight, shank length, body girth, back length, thigh length, beak length, comb length, and wattle length were collected from 250 local chickens. DNA isolated from blood of 1,440 local chickens was used for SNP genotyping with the Affymetrix chicken 600k SNP chip. Principal compo nent analysis showed that Forest and Coastal Savannah birds were closely related. Gener ally, all three ecotypes exhibited high genetic diversity, especially birds from the Interior Savannah zone. Morphological characterisation showed that ecotype (p = 0.016) and sex (p = 0.000) had significant effects on body weight. Birds of the Interior Savannah ecotype were the heaviest (p = 0.004), with mean weights of 1.23 kg for females and 1.40 kg for males. Sex also had a strong significant effect on most of the morphological measurements, but the sex * ecotype interaction effect was not significant. Very few of the feather phenotypes pre viously reported to be associated with heat resistance–frizzle (2%) and naked neck (1.6%)– were found in the studied populations. It is concluded that the three local ecotypes are genetically diverse but with similar morphological features and the information provided would be useful for future selection decisions.
Research Article
Keywords: Genotypic; Phenotypic; Local Chicken Ecotypes; Ghana